Sports Dentistry: A Literature Review (Journal of Pharmaceutical Negative Results, 2022)
Sports competitions and recreational activities are practiced by infants, kids, and teenagers for their physical and mental health.Unfortunately, engaging in sports increases the chance of suffering trauma to the mouth's delicate and hard tissues, including lacerationsto the lips, various injuries to the gingiva, tongue, or mucosa, chipped, luxated, or avulsed teeth, maxillary or mandibular fractures.The importance of the dentistry profession in connection to the prevention of dental and other orofacial sporting injuries has increaseddue to the popularity of contact sports and the encouraging of participation at a young age. Inculcating the prevention, management,and treatment of oral and face injuries, sports dentistry is the newest and most promising area of dentistry. Dentists should make it apoint to tell parents about the orofacial damage caused by sports and about the different preventive measures that are available. Theyshould also have solid clinical understanding of sports-related dentofacial injuries. In this article, we go over the different facets ofsports-related injuries as well as the risk factors that go along with them.